FEATURES OF DIGITAL MARKETING IMPLEMENTATION IN THE CONSTRUCTION INDUSTRY - Pushkar, T.; Zhovtiak, H.; Serohina, D. (Municipal economy of cities. Series: «Economy science», 2024)
The article is devoted to the topical issue of implementing forms and methods of digital marketing in construction. The purpose of the study is to substantiate the peculiarities of applying forms and methods of digital marketing in construction and to determine the impact of the specifics of construction enterprises on the feasibility of their application. While conducting the study, the authors used such scientific research methods as generalisation, comparison, analysis, and synthesis. We analysed the features of construction production and construction products that influence the formation of a digital marketing complex at construction enterprises and organisations, among which are the length of the construction production cycle, high capital intensity and cost of construction products, a significant level of concentration in the markets of construction products and services, long service life, and territorial definition of construction objects. The article outlines the main tasks solved by the introduction of a digital marketing complex at construction enterprises: conducting prompt and efficient marketing research, monitoring construction markets online, identifying effective advertising measures, forming a positive image of a construction enterprise, positioning its brands, and increasing transparency and openness of activities. It substantiates that the feasibility of applying forms and methods of digital marketing in construction depends on the type of construction (new construction, reconstruction, overhaul, and technical re-equipment), the scope of activity of a construction company (industrial construction, civil construction, residential construction), and the specifics of construction production. The authors identify the major marketing solutions and methods that allow their implementation based on the specific features of the construction company’s activities, the technological features of construction, and the current situation in the construction markets.